A pulmonologist's guide to understanding network meta-analysis. Issue 1 (5th July 2018) - Dobler, Claudia C.; Wilson, Michael E.; Murad, M. Hassan
Network meta-analysis allows comparisons between interventions, even in the absence of head-to-head trials http://ow.ly/exI630kfB4m